2016
DOI: 10.2495/cmem-v4-n4-522-531
|View full text |Cite
|
Sign up to set email alerts
|

Computational study of diffuser augmented wind turbine using actuator disc force method

Abstract: In this paper, a computational approach, based on the solution of Reynolds-averaged-Navier-Stokes (RANS) equations, to describe the flow within and around a diffuser augmented wind turbine (DAWT) is reported. In order to reduce the computational cost, the turbine is modeled as an actuator disc (AD) that imposes a resistance to the passage of the flow. The effect of the AD is modeled applying two body forces, upstream and downstream of the AD, such that they impose a desired pressure jump. Comparison with exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…The experimental data is consistent with the simulation results [16]. The small differences between experiment data and numerical calculation may, amongst others, be explained by the small wind tunnel blockage effect.…”
Section: Global Velocity Field In Unloaded Diffuser and Loaded Diffusersupporting
confidence: 80%
“…The experimental data is consistent with the simulation results [16]. The small differences between experiment data and numerical calculation may, amongst others, be explained by the small wind tunnel blockage effect.…”
Section: Global Velocity Field In Unloaded Diffuser and Loaded Diffusersupporting
confidence: 80%
“…When compared with experimental results, for a similar configuration but without forced transition, good agreement is found. As a matter of fact, Dighe et al [14] reported a value of C t equal to 0.81 using the same duct geometry and a porous disc to mimic the isolated rotor.…”
Section: Grid Resolution Studymentioning
confidence: 99%
“…They confirmed that embedding an actuator disk within a duct alters the power coefficient and that the interaction affects the actuator loading at which the optimal power coefficient is reached. As a consequence, the coupling of a rotor with optimal thrust coefficient with a duct might result in a non-optimal ducted wind turbine [14,15]. The discussed analytical models are based on the assumption of an uniformly loaded actuator disk, which is not representative of realistic rotors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several approaches to solve the flow equations around an AD. One of these approaches is based on the use of classical Computational Fluid Dynamics (CFD) techniques [1][2][3][4] and for this reason it will be named CFD-AD [5][6][7][8][9][10][11]. In this method, the Euler (or Navier-Stokes) equations are solved by finite volume or difference schemes, while the presence of the turbine is modelled by activating the momentum source terms in a disk-shaped region.…”
Section: Introductionmentioning
confidence: 99%